Treatment of Plasmodium chabaudi parasites with curcumin in combination with antimalarial drugs - Rosário, Virgilio Estólio do (2021)
Antimalarial drug resistance remains a major obstacle in malaria control. Evidence from Southeast Asia shows that resistance to artemisinin combination therapy (ACT) is inevitable. Ethnopharmacological studies have confirmed the efficacy of curcumin against Plasmodium spp. Drug interaction assays between curcumin/piperine/chloroquine and curcumin/piperine/artemisinin combinations and the potential of drug treatment to interfere with the ubiquitin proteasome system (UPS) were analyzed. In vivo efficacy of curcumin was studied in BALB/c mice infected with Plasmodium chabaudi clones resistant to chloroquine and artemisinin, and drug interactions were analyzed by isobolograms. Subtherapeutic doses of curcumin, chloroquine, and artemisinin were administered to mice, and mRNA was collected following treatment for RT-PCR analysis of genes encoding deubiquitylating enzymes (DUBs). Curcumin was found be nontoxic in BALB/c mice. The combination of curcumin/chloroquine/piperine reduced parasitemia to 37% seven days after treatment versus the control group's 65%, and an additive interaction was revealed. Curcumin/piperine/artemisinin combination did not show a favorable drug interaction in this murine model of malaria. Treatment of mice with subtherapeutic doses of the drugs resulted in a transient increase in genes encoding DUBs indicating UPS interference. If curcumin is to join the arsenal of available antimalarial drugs, future studies exploring suitable drug partners would be of interest.